(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
The primary objective of this research was to examine the impact of sustainability reporting disclosure on the complexity of financial reports and its effect on the cost of equity in a sample of banks listed on the Iraq Stock Exchange. The research analyzed the financial reports of the banks in the sample for the period 2012–2022, encompassing 10 banks and comprising 110 observations. The research employed manual content analysis to analyze the texts and extract quantitative and qualitative data related to the research variables. The findings revealed a significant impact of sustainability reporting disclosure on the cost of equity, while the complexity of financial reports did not mediate this impact. The research recommends that accounting bodies and organizations responsible for regulating accounting practices raise employee awareness of the importance of sustainability as a means of achieving company value, and address the issue of financial report complexity due to its impact on users.